From violent victims to emancipatory agency of peace: exploring female Jirga as local gendered peace formation and community peacebuilding in Khyber Pakhtunkhwa, Pakistan - Khan, Irfan (Penerbit Universiti Kebangsaan Malaysia, 2022)
For years, the insecurity and violence against women in many parts of Pakistan have magnified the danger of the prevalent worldview of strong and protective men. In contrast, women are weak and protected by men. Inevitable victimisation and powerless women are counterproductive since women are central to the community's household institution. This paper explores local community peacebuilding initiatives of women's first Jirga by a local activist Tabassum Adnan in Pakistan's Province of Khyber Pakhtunkhwa. Exploring women's Jirga as an agency of regional and gendered peace formation in a salient patriarchal Pakhtun worldview underscores women's security and gendered Peace perspective in recognising the need to consider the missing systemic and unpeaceful change and transformation in contemporary Pakistan and South Asia. Adopting qualitative methods of Feminist Peace research unravels the potential and pitfalls of how women can embark upon alternative dispute resolutions (ADR) when patriarchal conceptualisations of conflict resolution prevent their active participation. Findings show multidimensional links between local community peace and global systemic and peaceful transformation of international relations (IR). Recognising the transformative roles of women in overcoming GBV is a critical transnational shift from the past and minimal human rights protection of women to the present and maximal recognition of women as emancipatory agents of peace.